Colon-specific delivery of 5-fluorouracil from zinc pectinate spheroids through in situ intra-capsular ethylcellulose- pectin plug formation / Assad Ali Faraj Elyagoby - Elyagoby, Assad Ali Faraj (Institute of Graduate Studies, UiTM, 2014)
Conventional fluid-bed and immersion film coating of hydrophilic zinc pectinate spheroids using ethylcellulose-pectin mixture is met with fast drug release due to hydrophobic ethylcellulose coat detachment. This study explored in situ intra-capsular spheroid coating for colon-specific delivery of 5-fluorouracil. The solid coating powder was constituted of ethylcellulose and pectin in weight ratios of 11:0 to 2:9. Its weight ratio to spheroids was varied between 2:3 and 3:2. Delayed 5-fluorouracil release was obtained when the weight ratio of ethylcellulose and pectin in coating powder was kept at 8:3, and weight ratio of solid coating powder to spheroids was kept at 3:2 with particle size of ethylcellulose reduced to 22 μm.